The impact of maintenance and technology change on remanufacturing as a recovery alternative for used wind turbines (2015)
In the wind power industry, maintenance and technological evolution/improvement are critical factors to ensure low operations and maintenance (O&M) costs and keep the wind turbine (WT) available to generate power. In addition, these factors are critical in facilitating product recovery through remanufacturing at the end-of-use (EOU). Under a system dynamics (SD) approach, the interaction between maintenance, reliability, and technological obsolescence on the remanufacturing of a wind turbine was modeled. Findings suggest that regular preventive maintenance might avoid/slow functional obsolescence, and as a result, the remanufacturing cost is reduced. Technological change could lead to technological obsolescence. Both types of obsolescence might increase the overall remanufacturing cost. An increased remanufacturing cost will affect the attractiveness for recovery and profits obtained from original equipment manufacturers and the savings in the initial capital investment made by secondary customers.